Actualization business process modeling of enterprises of main gas transportation - Кузьмина, В. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Brief overview of the current state of Ukraine's gas transit system were analyzed studies the definition of "business process" and adopt the definitions of L. Denisenko, contains a description of the business process of modeling and their brief classification is proposed to use graphical business process formalization of the main transport natural gas, allowing illustrate their composition and structure for the definition of 'bottlenecks' in order to improve the functioning of the business enterprise system as a whole.